2018
DOI: 10.15406/ipmrj.2018.03.00096
|View full text |Cite
|
Sign up to set email alerts
|

Flossing bands to treat keinböck’s disease in a collegiate men’s basketball player: a case report

Abstract: Background: Keinböck's disease (KD) is an uncommon medical condition characterized by avascular necrosis of the lunate. Conservative treatment of this condition consists of immobilization, strengthening and range of motion (ROM) exercises of the surrounding musculature of the wrist. Tissue flossing is a relatively new treatment technique that incorporates wrapping latex bands around the targeted body part, followed by a brief period of exercise. Tissue flossing is thought to provide similar therapeutic effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…However, as this case study was not a controlled study, it cannot be established if the improvement in pain was due to the floss band treatment, the lacrosse ball massage (or the combination), or even a placebo effect. A further case study reported a significant improvement in Kienböck's disease (in the visual analog scale and wrist/hand disability index) of a 21 year-old male basketball player following a 6 week period of wrist flossing (Cage et al, 2018). With regard to Osgood-Schlatter's disease, an additional case study reported improvement in both pain and muscle function following a 9 week floss band intervention at the knee joint of a 14 year-old male soccer player (Weber, 2018).…”
Section: The Impact Of Flossing On Disease Pain and Injurymentioning
confidence: 92%
“…However, as this case study was not a controlled study, it cannot be established if the improvement in pain was due to the floss band treatment, the lacrosse ball massage (or the combination), or even a placebo effect. A further case study reported a significant improvement in Kienböck's disease (in the visual analog scale and wrist/hand disability index) of a 21 year-old male basketball player following a 6 week period of wrist flossing (Cage et al, 2018). With regard to Osgood-Schlatter's disease, an additional case study reported improvement in both pain and muscle function following a 9 week floss band intervention at the knee joint of a 14 year-old male soccer player (Weber, 2018).…”
Section: The Impact Of Flossing On Disease Pain and Injurymentioning
confidence: 92%